WORK MOTIVATION OF HOTEL COMFORT HOUSEKEEPING DUMAI EMPLOYEES - Daniel Moses; Andi Moh Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Motivation is a very important factor in a company, because it can improve employee work discipline. So that the ability of management to provide motivation will greatly determine the success or failure in achieving company goals. Researchers conducted research in a 3 star hotel in the city of Dumai, Riau province, namely Comfort. Researchers conduct research that aims to find out how employee motivation and how hotels increase employee motivation. The research will be known and measured by quantitative descriptive methods. This study took a sample of 18 respondents. Data collection techniques in this study used observation, questionnaires, documentation, interviews. To measure the data interval in this study using a Likert scale. Based on the results of the study showed that the work motivation of Dumai Comfort Hotel Housekeeping employees is included in the good category because the employee supervisors also provide good efforts to increase the motivation of their employees.  Keywords : Motivation, Housekeeping, Hotel.